Dynamic Metabolic Changes during the First 3 Months after 90Y-Ibritumomab Tiuxetan Radioimmunotherapy - Miwako Takahashi; Toshimitsu Momose; Keitaro Koyama; Motoshi Ichikawa; Mineo Kurokawa; Kuni Ohtomo (The Scientific World Journal)
Objective. To elucidate the time course of tumor metabolism during the first 3 months after 90Y-ibritumomab tiuxetan radioimmunotherapy (RIT) in patients with refractory malignant lymphoma. Materials and Methods. Seven patients with recurrent follicular lymphoma underwent FDG-PET imaging before and after 1-, 4-, and 12-week RIT with 90Y-ibritumomab tiuxetan. Tumor metabolic activity on FDG-PET scans was assessed as the maximum standard uptake value (SUVmax). Results. Decrease in metabolism was detected 1 week after RIT. In the most decreased lesion, SUVmax decreased to 20% of the baseline value during the first week. Most lesions continued to decrease for up to 4 weeks. Some lesions showed increased metabolism from 4 to 12 weeks, while the level of FDG accumulations at 12 weeks was still lower than the baseline. Conclusions. Tumor response to RIT could be observed as early as 1 week after the administration of RIT. After tumor activity decreases, the metabolism may increase at least between 4 and 12 weeks. It suggests that the metabolic changes should be carefully evaluated during this period.